Analysis of Path Coefficient and Genetic Divergence for Yield and its Components in Pigeon Pea [Cajanus cajan (L.) Millsp.] Genotypes - Mourya, Alok Kumar; Srivastava, Arvind Kumar; Srivastava, Aman; Nikhil,; Singh, Aditi; Singh, Supriya; Veersain,; Kumar, Soyal (International Journal of Bio-resource and Stress Management, 2025)
The present investigation was conducted during August, 2021–April, 2022 at Oilseed Research Farm, Kalyanpur, C. S. Azad University of Agriculture and Technology, Kanpur, U.P., India, to work out the character relationship among yield and contributing traits and to know the direct and indirect effect of different character on seed yield plant-1 through path coefficient analysis. Path coefficient analysis was done by using seed yield as dependent variable and ten other quantitative characters as independent variables, The analysis of path emphasized that the characters viz., plant height, days to 50% flowering, days to maturity, number of secondary branches, number of pods plant-1, biological yield, harvest index and 100 seed weight showed positive and direct effect on seed yield at genotypic level and phenotypic level, should be taken into consideration for formulating selection breeding programme in order to bring about improvement in the populations. The genetic divergence by Tocher’s method for seed yield and it’s component traits in pigeon pea genotypes. On the basis of genetic divergence under study, it was suggested that the crosses between cluster IV and cluster V, cluster II and cluster III be used for effective in hybridization breeding programme. The contribution of contribution of various characters towards the expression of genetic divergence were days to 50% flowering, days to maturity, number of branches per plant and 100 seed weight together contributed for about 95.44% of the total divergence.